Positive correlation between measures of habitual responding and motivated responding in mice. - Bryant, Kathleen G.; Barker, Jacqueline M. (Journal of the Experimental Analysis of Behavior, 2024)
Habit and motivation are thought to be separate processes, with motivated behavior often considered to be goal directed, whereas habits are defined by the absence of goal‐directed control over behavior. However, there has been increasing interrogation of the binary nature of habitual versus goal‐directed behavior. Furthermore, although drug and alcohol exposure can promote the formation of habits, drug seeking itself can also be highly flexible, pointing toward the need for complex consideration of the parallel processes that drive behavior. The goal of the current study was to determine whether there was a relation between motivation—as measured by progressive ratio—and habit—as measured by contingency degradation—and whether this relation was affected by ethanol exposure history and sex. The results showed that these measures were positively correlated such that greater contingency insensitivity was associated with achieving higher break points on the progressive‐ratio task. However, this relation depended on reinforcement schedule history, ethanol exposure history, and sex. These point to potential relations between measures of habit and motivation and stress the importance of carefully parsing behavioral findings and assays. These findings are also expected to inform future substance use research, as drug history may affect these relations.